AMPEROMETRIC METHOD OF ANALYSIS AND ITS ADVANTAGES OVER OTHER METHODS - G.G. Sadullayeva; Sh.B. Rakhmatov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In addition to directly determining the concentration of the analyte for the experiment, it is also used to find the equivalence point in the titration process. An amperometric titration is used. The essence of amperometric titration is to measure the values ​​of the diffusion current, which changes as a result of a change in the concentration of the analyte or titrant (reagent of known concentration). This method is called amperometric titration because the amplitude to be determined is the current measured in microamps (µA).